Seasonality in Daily Bond Returns - Jordan, Susan D.; Jordan, Bradford D. (Journal of Financial and Quantitative Analysis, 1991)
This paper tests for seasonal patterns in corporate bond returns using the Dow Jones Composite Bond Average. Each seasonal pattern documented for equities is investigated. For the period 1963–1986, corporate bond returns exhibit January, turn-of-the-year, and weekof-the-month effects, but no significant day-of-the-week or turn-of-the-month effects. In contrast, for the S&P 500 stock index, the turn-of-the-month and day-of-the-week effects are highly significant, but the week-of-the-month effect is less significant, and the January and turn-of-the-year effects are insignificant. The behavior of an equity index constructed using companies in the bond index is similar to that of the S&P, except the turn-of-the-year effect is significant.